GEOINFORMATION INTERACTIVE MOBILE MEDICAL SYSTEM - K. A. Ablyazov; L. K. Ablyazov; R. A. Singatulin (InterCarto. InterGIS, 2016)
Today, there are a significant class of personalized mobile systems (m-Health) to monitor the health of the person. These personalized systems are designed for remote collection of different biomedical data of a person and are mainly used with diagnostic purposes. Such systems are passive means of measuring, control and collection of biomedical information and have limited class of tasks. An emerging new class of personalized medical and biological systems based on advanced technology provides greater interaction wearable biosensors, of drugs and the human body, greater integration database of biomedical information systems, global positioning and neural networking with stationary medical centers in real time. Below discusses the concept of personalized medicine with the use of mobile technology and satellite systems of positioning. The description of one of the projects being developed in the laboratory of Information Technology, Saratov State University, personal remote-invasive medical system based on mobile applications.